Phase 1b study of cobimetinib plus atezolizumab in patients with advanced BRAFV600 wild-type melanoma progressing on prior anti–programmed death-1 therapy. (January 2023) - Sandhu, Shahneen; Atkinson, Victoria; Cao, Maria González; Medina, Theresa; Rivas, Ainara Soria; Menzies, Alexander M.; Caro, Ivor; Roberts, Louise; Song, Yuyao; Yan, Yibing; Guo, Yu; Xue, Cloris; et al.
Abstract: Objective: To evaluate the efficacy and safety of cobimetinib plus atezolizumab in the treatment of patients with advanced BRAF V600 wild-type melanoma who had progressed on prior anti‒programmed death-1 (PD-1) therapy. Patients and methods: This phase 1b, open-label, international multicentre study enrolled 3 cohorts. Herein, we report on patients in cohorts A and B who had progressed on prior anti‒PD-1 therapy. Patients in cohort A received cobimetinib 60 mg once daily for 21 days followed by a 7-day break and concurrent intravenous atezolizumab 840 mg every 2 weeks. Patients in cohort B received the same dosing regimen as cohort A except for cycle 1 in which patients received cobimetinib only for the first 14 days prior to initiation of atezolizumab on cycle 1 day 15. Coprimary end-points were objective response rate and disease control rate. Secondary end-points were duration of response, progression free survival and overall survival. Results: Between 19th June 2017 and 12th December 2018, 103 patients were enrolled. Median follow-up was 6.9 months (interquartile range, 4.8–10.1 months); objective response rate was 14.6% and disease control rate was 38.8% (95% confidence interval, 29.39–48.94). The median duration of response, progression-free survival and overall survival was 12.7 months, 3.8 months and 14.7 months, respectively. The most common adverse events were diarrhoea (75/103; 72.8%), dermatitis acneiform (57/103; 55.3%) and nausea (52/103; 50.5%). Thirty-four patients (33.0%) died: 33 (91.7%) due to progressive disease and one (1%) due to treatment-related oesophagitis. Conclusions: Combination therapy with cobimetinib and atezolizumab in patients with advanced BRAF V600 wild-type melanoma with disease progression on or after prior anti‒PD-1 therapy demonstrated limited activity. Clinical trial registration: This study is registered with ClinicalTrials.gov ; NCT03178851; Highlights: Treatment of advanced BRAF V600 -wild type melanoma after anti–programmed death-1 failure is challenging. Cobimetinib (C) + atezolizumab (A) combination was studied in this population. A + C showed limited activity in patients with relapsed refractory disease. The objective response rate was 14.6% and disease control rate was 38.8%. No new safety signals were identified.